2017
DOI: 10.1007/s00213-017-4595-8
|View full text |Cite
|
Sign up to set email alerts
|

Stress-related salivary alpha-amylase (sAA) activity in alcohol dependent patients with and without a history of childhood maltreatment

Abstract: The discrepancy between physiological responsivity and subjective stress experiences may account for an increased inability to cope with stressful situations, which in turn might explain the enhanced risk of relapse in AD patients with a history of CM during early abstinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Previous evidence suggests that dysregulation of the stress system in substance users more broadly may differ in direction, with stimulant (King et al, 2010; Moran-Santa Maria et al, 2010) and opioid (Back et al, 2015) users showing exaggerated stress responding, while alcohol (Muehlhan et al, 2017, 2018) and cannabis users appear to have blunted stress responding relative to controls. These findings underline the likely complexity in the mechanisms of these differences, with various factors potentially contributing to observed differences including pre-existing factors, uncontrolled differences in psychiatric comorbidities between drug-using groups and controls, and acute, residual, and chronic drug effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous evidence suggests that dysregulation of the stress system in substance users more broadly may differ in direction, with stimulant (King et al, 2010; Moran-Santa Maria et al, 2010) and opioid (Back et al, 2015) users showing exaggerated stress responding, while alcohol (Muehlhan et al, 2017, 2018) and cannabis users appear to have blunted stress responding relative to controls. These findings underline the likely complexity in the mechanisms of these differences, with various factors potentially contributing to observed differences including pre-existing factors, uncontrolled differences in psychiatric comorbidities between drug-using groups and controls, and acute, residual, and chronic drug effects.…”
Section: Discussionmentioning
confidence: 99%
“…Dependent prescription opioid users show heightened subjective but not physiological stress responding following an acute social stressor compared with controls (Back et al, 2015). By contrast, recently detoxified alcohol-dependent patients exhibit decreased hormonal stress responding relative to healthy controls after exposure to similar stress (Muehlhan et al, 2017, 2018).…”
Section: Introductionmentioning
confidence: 97%
“…The literature examining the moderating effect of ELA on various addictive processes is small but growing. Acute socio-evaluative stress has resulted in blunted sympathetic activity in those who abuse alcohol, though in this context there was no effect of ELA (Muehlhan, Hocker et al 2017). Acute stress in a controlled setting (socio-evaluative stress) increases craving for prescription opioids (Back, Gros et al 2015) and tobacco (al’Absi et al, 2017).…”
Section: Introductionmentioning
confidence: 89%
“…Chronic alcohol use is linked to chronic alterations in the hypothalamic‐pituitary‐adrenal (HPA) axis and the sympathetic adrenal medullary system (Koob & Kreek, 2007), which are associated with relapse (Koob et al., 2020; Sliedrecht, de Waart, Witkiewitz, & Roozen, 2019). Numerous studies have found that alcohol use globally perturbs stress system sensitivity at baseline and resting state (Blaine & Sinha, 2017; Gilpin & Weiner, 2017; Lu & Richardson, 2014; Muehlhan et al., 2017; Seo et al., 2013). They have also shown blunted stress‐induced HPA axis activation compared to non‐users (Lovallo, 2006).…”
Section: Introductionmentioning
confidence: 99%